Tren Penilaian Formatif dan Portofolio untuk Pendidikan Dasar: Solusi Pengganti Ujian Standar - Ramadhani, Nur Aisyah; Pratama, Rizki Ananda; Putri, Elena Maharani (FONDASI: Jurnal Pendidikan Dasar, 2026)
Standardized testing systems in primary education are increasingly criticized for their inability to comprehensively measure 21st-century competencies. This study aims to analyze trends in formative and portfolio assessment as alternatives to standardized tests in primary education contexts. This research employs a systematic literature review approach of 30 scientific articles published between 1990-2025, focusing on the implementation of formative and portfolio assessment in primary education. Findings indicate that portfolio assessment enhances student engagement in learning processes, provides a holistic view of competency development, and supports constructivist learning principles. Formative assessment integrated with technology (e-portfolios) proves effective in providing continuous feedback and authentically documenting students' learning progress. Formative and portfolio assessment offer a more comprehensive, humanistic approach aligned with 21st-century competency demands compared to traditional standardized tests, although implementation requires adequate teacher preparation and infrastructure support.